Multimodal Visualization of the Left Ventricular Postinfarction Aneurysms: Current State of the Problem and Own Observation Results - Svitlana V. Fedkiv; Sergiy V. Potashev; Olha M. Unitska; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. Left ventricular aneurysm (LVA) is a complication occurring in 5–10% of acute myocardial infarction (AMI) patients significantly complicating AMI acute stage course and leading to advanced congestive heart failure (CHF) progress. Non-invasive LVA visualization includes echocardiography, cardiac magnetic resonance imaging (MRI), radio-nuclide ventriculography, and multi-slice computed tomography (MSCT). It can also be detected during heart catheteriza-tion by coronary ventriculography (CVG). Each method has its advantages and drawbacks.The aim. To analyze multimodal non-invasive LVA visualization methods (echocardiography and MSCT) in order to establish accuracy of these methods compared to CVG regarding the diagnosis of LVA and LVA thrombosis.Methods. We examined 60 patients after AMI with LVA admitted for surgical revascularization and left ventricular aneurysm resection (LVAR). Control group included 110 patients after AMI prior to revascularization without history of LVA. All the patients underwent CVG, heart MSCT and echocardiography prior to surgery.Results. Mean patients’ age was 60.9±11.4 years (46 [76.7%] men and 14 [23.3%] women, mean LVEF was 42.7±11.1%. Significant CAD according to coronary angiography (CAG) before surgery was proved in 59 (98.3%) pa-tients, and 1 (1.7%) patient had no significant coronary lesions. The majority of patients had anterior LVA localization after AMI in LAD area (57 [95.0%] patients), 2 (3.3%) patients were diagnosed with inferior LVA after AMI in RCA area, and 1 (1.7%) patient had posterior-lateral LVA in Cx area. There was high correlation between LVEF obtained with echo-cardiography and that obtained with MSCT (r=0.955, p<0.0001), although mean LVEF obtained with echocardiography was significantly higher compared to MSCT results (42.7±11.1% vs. 32.7±9.3%, p<0.0001). Comparison of accuracy of the methods in LVA diagnosis showed that MSCT was the most precise method with significantly higher sensitivity compared to CVG and echocardiography (94.9% vs. 75.0%, p=0.002, and 88.0%, p=0.023, respectively), and MSCT significantly ex-ceeded CVG in all diagnostic method accuracy indices. Echocardiography also significantly exceeded CVG in all diagnostic accuracy indices. Comparison of accuracy of the methods in LVA thrombosis diagnosis showed similar results: echocar-diography was much more precise in terms of sensitivity (79.4% vs. 58.8%, p<0.0001) and the rest of indices. MSCT was much more precise in terms of all indices compared to CVG, and also significantly exceeded echocardiography results in terms of sensitivity (97.1% vs. 79.4%, p<0.0001), positive (PPV) (100.0% vs. 93.1%, p=0.0005) and negative predictive value (NPV) (99.1% vs. 93.9%, p=0.0091), integral “area under curve” index (AUC) (0.99 vs. 0.89, p=0.0001) and odds ratio (OR) (3630 vs. 208, p<0.0001).Conclusions. High correlation of LVEF according to echocardiography and MSCT results allows to skip CVG as a global LV contractility evaluation method enabling to reduce the procedure time. The lowest accuracy of CVG in the diagnosis of LVA and LVA thrombosis also allows to reduce the duration and volume of the invasive procedure to selective CAG and to reduce radiation exposure for patients and operators in favor of non-invasive and more accurate methods (MSCT and echocardiography). MSCT is the most accurate method for LVA thrombosis diagnosis, but it is completely comparable to echocardiography in LVA diagnosis per se, making echocardiography the method of choice in screening and stratification of patients after AMI regarding myocardial revascularization only or combined surgical revascularization with LVAR due to its rapidness, low cost and absence of patient-related adverse effects.